Financial sector convergence in the ASEAN economies - Ibrahim, Juliana; Habibullah, Muzafar Shah; Radam, Alias; Kaliappan, Shivee Ranjanee (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The Association of South East Asian Nation (ASEAN) is one example of regionalism in the Asian region. The purpose of this study is to address the question whether its formation has been successful or remains heterogeneous. By applying annual financial data for the period 1999 to 2009, on average, our panel unit root tests result suggests that the ASEAN countries financial depth (financial intermediation) are catching-up convergence towards their average and benchmark (Singapore) levels. In this respect, the government of the ASEAN countries are expected to continue with their initiatives in promoting the financial integration towards achieving a stable economic environment for investment and other productive economic activities in Asia.